1980
DOI: 10.1073/pnas.77.6.3499
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule assembly and conanavalin A capping in lymphocytes: reappraisal using normal and abnormal human peripheral blood cells.

Abstract: We have analyzed the assembly of microtubules and the distribution of concanavalin A (Con A)-receptor complexes in the same populations of human peripheral blood T and B lymphocytes. We hoped to resolve the prolonged controversy over the relationship of microtubules to Con A cap formation in lymphocytes and to explain the abnormally high spontaneous and colchicine-induced Con A capping that was observed recently in lymphocytes from a patient with an inherited form of severe combined immunodeficiency disease (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…(42) have shown that colchicine is able to induce macrophages to accumulate phagocytic and pinocytic vesicles as well as Con A receptors into a cap structure at one pole of the cell . The primary mode of action of colchicine has been commonly considered to involve the disassembly of microtubules (4,5,22,27,44). However, colchicine has also been found to affect several other cellular activities (e .g., nucleoside transport and membrane components) (25,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…(42) have shown that colchicine is able to induce macrophages to accumulate phagocytic and pinocytic vesicles as well as Con A receptors into a cap structure at one pole of the cell . The primary mode of action of colchicine has been commonly considered to involve the disassembly of microtubules (4,5,22,27,44). However, colchicine has also been found to affect several other cellular activities (e .g., nucleoside transport and membrane components) (25,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Such a concept has come mainly from the study of drug effects on the distribution of cell surface proteins. The drugs used include microtubuledepolymerizing agents such as colchicine, nocodazole, and vinblastine (2,4,6) and microfilament-depolymerizing agents such as cytochalasin B (4,8). The distribution of immunoglobulins and concanavalin A receptors on lymphocytes (3,4,6) and fibroblasts (1) after treatment with such drugs has been extensively studied by fluorescence microscopy.…”
mentioning
confidence: 99%
“…It now has been generally accepted that the lateral mobility and distribution of externally exposed cell surface proteins are regulated in large part by submembranous cytoskeletal elements (1)(2)(3)(4)(5)(6), although there is also some evidence that directed lipid flow in membranes is important as well (7). Such a concept has come mainly from the study of drug effects on the distribution of cell surface proteins.…”
mentioning
confidence: 99%
“…This proposal is not without precedent . Abnormal cytoskeleton and membrane properties have already been suggested in lymphocytes from patients with two other forms of severe immune dysfunction (6,25) .…”
Section: Discussionmentioning
confidence: 99%